Duration of reverse remodeling response to cardiac resynchronization therapy: Rates, predictors, and clinical outcomes. (15th September 2017) - Oka, Takafumi; Inoue, Koichi; Tanaka, Koji; Toyoshima, Yuko; Isshiki, Takaaki; Kimura, Takeshi; Nobuyoshi, Masakiyo; Shizuta, Satoshi; Arita, Takeshi; Fujii, Satoki; Iwakura, Katsuomi; Fujii, Kenshi; et al.
Abstract: Background: A subset of patients undergoing cardiac resynchronization therapy (CRT) for heart failure (HF) with severe left ventricular (LV) dysfunction experience only short-lived LV reverse remodeling. Little is known about the incidence and prognosis of this finding. We sought to identify predictors of a brief response and investigated the prognosis in a retrospective study. Methods: A total of 528 patients from a Japanese multicenter database with full echocardiography datasets were enrolled. Follow-up was 3.4 ± 1.3 years. Based on relative reduction in LV end-systolic volume (LVESV) at 6 months, we categorized patients as responders (reduction in LVESV ≥ 15%) and non-responders (NRs; reduction in LVESV < 15%). Based on reduction in LVESV at 1–2 years, responders were subdivided into long-lasting responders (reduction in LVESV ≥ 15%) and brief responders (reduction in LVESV < 15%). Results: Of 328 responders, 50 (15%) were brief responders. Predictors of brief response were prior ventricular tachyarrhythmia, a non-left bundle-branch block (LBBB) intrinsic QRS pattern, and prior hospitalization for HF. The risk of all-cause death in brief responders was significantly lower than that in NRs ( P  = 0.034) and tended to be higher than that in long-lasting responders ( P  = 0.080). Conclusions: Approximately 15% of responders were brief responders. Prior ventricular tachyarrhythmia, a non-LBBB pattern, and HF hospitalization were independent predictors of a brief response. Brief response was significantly associated with decreased risk of all-cause death compared with NRs and had a tendency toward increased risk of all-cause death compared with long-lasting responders.